Gifts of Virtue, Alice Walker, and Womanist Ethics - Harris, M. author. aut Link
XII, 178 p.
Keywords: Melanie L. Harris dives into the spirituality and life work of Alice Walker, literary genius and poet. Through the lens of Womanist ethics, Harris takes an inside look into the virtues and values that can be lifted from a study of Walker s non-fiction work. This work enlivens the debate in African and African American religious thought about the fluidity of spirituality and widens the conversation to encourage readers to embrace religious traditions inclusive of and beyond Christianity as the foundations for empowerment of both women and ethical values.